2017
DOI: 10.1007/s11274-017-2222-9
|View full text |Cite
|
Sign up to set email alerts
|

The change of the state of cell membrane can enhance the synthesis of menaquinone in Escherichia coli

Abstract: Menaquinone (MK) was an attractive membrane-bound intracellular chemical. To enhance its production, we tried to find the relationship between its synthesis and the state of cell membrane in producing strain. Due to non-ionic surfactant-polyoxyethylene oleyl ether (POE) and plant oil-cedar wood oil (CWO) can typically increase extracellular secretion and intracellular synthesis of MK respectively, the effect of these two substances on cell morphology, physical properties of cell membrane was investigated. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Maintenance of appropriate membrane fluidity is vital to membrane function. In general, membrane fluidity trends with the relative abundance of unsaturated lipids (43), though other membrane components can also contribute to this property (16,44,45). Membrane fluidity was measured via cell membrane fluorescence polarization, where increased polarization corresponds to decreased membrane fluidity (9,46).…”
Section: Resultsmentioning
confidence: 99%
“…Maintenance of appropriate membrane fluidity is vital to membrane function. In general, membrane fluidity trends with the relative abundance of unsaturated lipids (43), though other membrane components can also contribute to this property (16,44,45). Membrane fluidity was measured via cell membrane fluorescence polarization, where increased polarization corresponds to decreased membrane fluidity (9,46).…”
Section: Resultsmentioning
confidence: 99%
“…It was, however, apparent that the increase in MK–7 concentration is not merely a reflection on cell density. Binding of IONs@APTES to B. subtilis might have changed the state or composition of cell membranes, resulting in enhanced secretion of MK–7 to the fermentation medium [ 7 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptomic analysis showed that the pathways such as ABC transporters, bacterial chemotaxis, and oxidative phosphorylation changed significantly, indicating that the respiratory system and state of the cell membrane were changed obviously in SinR quad . A previous study discovered that changing the state of the membrane in Escherichia coli could increase the synthesis of MK-8 [ 62 ]. Our study verified this prediction by quantitatively determining the membrane potential and respiration of SinR quad and BS168.…”
Section: Discussionmentioning
confidence: 99%